On the comparison of dollar‐unit and stratified mean‐per‐unit estimators - DUNMORE, PAUL V. (Contemporary Accounting Research, 1986)
Abstract. The paper discusses the findings reported by Smieliauskas (1986) and expands on them. It focuses on the dominance criterion for cost efficiency and on the usefulness of power curves for stratified mean‐per‐unit estimators. The analyses lead to the conclusions that: (1) while an audit plan which dominates another is associated with lower cost, a plan with lower cost does not necessarily dominate: (2) the distribution function of the t statistic becomes normal for sufficiently large samples, but the approach to normality is not necessarily uniform as sample size increases; (3) large sample size is required for nominal confidence levels to be a good approximation to the true confidence level, and the true confidence level can move temporarily farther from the nominal level as the sample size increases; and (4) the lack of reliability of ex ante power curves for the stratified mean‐per‐unit estimator makes it difficult to decide which power curve dominates. Résumé. Cet article discute des résultats publiés par Smielauskas (1986) et les extrapole. Il met l'accent sur le critère de dominance pour l'efficacité des coûts et sur l'efficacité des courbes de puissance pour les estimateurs de moyenne‐par‐unité stratifiée. Les analyses portent à conclure que: (1) même si un programme de vérification dominant par rapport à un autre est associé à un coût inférieur, un programme à coût inférieur n'est pas nécessairement dominant; (2) la fonction de distribution de la statistique t tend vers la normale pour des échantillons suffisamment grands, mais ce rapprochement vers la normalité n'est pas nécessairement uniforme à mesure que la taille de l‘échantillon devient plus grande; (3) un échantillon de grande taille est requis afin que les seuils de confiance “nominaux” constituent une bonne approximation du seuil de confiance “réel”, et le seuil de confiance “réel” peut s’éloigner temporairement du seuil de confiance “nominal” à mesure que s'accroît la taille de l‘échantillon; et (4) l'absence de fiabilité des courbes de puissance ex ante pour l'estimateur de moyenne‐par‐unité stratifiée rend ardue la sélection de la courbe de puissance dominante.